Bridging Socio-Economic Disparities Through Educational Infrastructure: A Bibliometric Analysis - Hasmirati (Mimbar Ilmu, 2024)
Educational infrastructure has become a crucial pillar in addressing socio-economic disparities. This study systematically examines theories related to educational infrastructure and explores the current state of research and its application using a visual bibliometric analysis method based on data from 1846 to 2024. The analysis reveals that educational infrastructure has been a global concern for over a century. The analyzed articles reflect contributions from 2,873 authors and were published in 237 different journals, highlighting diverse research perspectives. The study finds that publications addressing the contribution of educational infrastructure to socio-economic disparities have significantly increased, particularly since 2015. This indicates that educational infrastructure development is a multidisciplinary research area gaining growing attention. At the national level, developing countries have become more active in improving their educational infrastructure, striving to catch up with or even surpass some developed countries in terms of educational access and quality. Cluster analysis results indicate that existing research focuses on inclusive education integration, aiming to solve issues related to educational accessibility and quality and providing better solutions to enhance educational equity. The study concludes that educational infrastructure development can be a key factor in reducing socio-economic disparities and supporting sustainable community development. These findings strengthen the understanding of the relationship between educational infrastructure and socio-economic inequality while offering policy guidance and future research directions to create an inclusive and equitable education system.